Impact of iodine nutritional levels in urban and rural pregnant women on neonatal growth indicators: a cohort study in Xinjiang, China - Zhou, Jing; Tayier, Rishalaiti; Abuduwaili, Dannier; Muhetaer, Dawureni; Wang, Chenchen; Pan, Kai (Frontiers in Nutrition, 2025)
ObjectivesIodine nutrition during pregnancy is crucial for infant health. This study aimed to investigate regional heterogeneity in iodine nutrition levels among urban and rural/agro-pastoral women and its association with neonatal growth indicators, providing evidence for region-specific nutritional interventions.MethodsThe study enrolled 85 urban pregnant women from Urumqi City and 181 rural/agro-pastoral pregnant women from the Ili Kazakh Autonomous Prefecture. Basic demographic data were collected via questionnaires, and maternal serum and random urinary iodine concentrations were determined using whole blood and urine samples collected during early to mid-pregnancy. After balancing baseline differences between urban and rural groups using inverse probability weighting, the relationship between maternal iodine nutrition and neonatal birth outcomes, as well as its regional interaction effects, were analyzed.ResultsThe median serum iodine levels in urban and rural/agro-pastoral pregnant women were 84.44 (75.50, 97.10) μg/L and 246.41 (186.33, 322.54) μg/L, respectively, showing a significant difference (p < 0.05). Regional interactions were observed between maternal serum/urinary iodine levels and neonatal birth length. In rural/agro-pastoral regions, iodine nutrition exhibited a nonlinear association with neonatal length (optimal serum iodine range: 100.62–254.20 μg/L; optimal random urinary iodine range: 106.16–210.80 μg/L). In contrast, urban pregnant women mostly displayed linear or nonsignificant associations between iodine levels and neonatal growth indicators.ConclusionThe impact of maternal iodine nutrition on neonatal growth differs between urban and rural/agro-pastoral areas. A nonlinear association with an optimal range was observed between iodine nutrition and neonatal length in rural/agro-pastoral regions. These findings provide a basis for developing region-specific iodine nutrition intervention strategies. It should be noted, however, that the urban group had a relatively small sample size, and the statistical power for between-group comparisons was limited. Therefore, the conclusions warrant further validation.